2018
DOI: 10.3390/vetsci5020058
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Learning: Assessment of the Veterinary Virtual Anatomy Education Software IVALA™

Abstract: Although cadaveric dissection has historically been the cornerstone of anatomical education, it comes at the cost of some emotional, moral, safety, and environmental concerns. Computer assisted learning (CAL) programs are an increasingly common solution to these issues; however, research regarding the efficacy of high fidelity simulation is limited. The traditional first semester veterinary gross anatomy course curriculum at Ross University School of Veterinary Medicine (RUSVM) was supplemented with a web base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
1
24
0
2
Order By: Relevance
“…28,29 The BL format was evaluated very positively by the students through all three semesters; this again agrees with previous studies. [7][8][9][10] We think that a great impact to the successful implementation and acceptance of this delivery format was given by the predetermined order of action within the BL. The task to address the problem individually first, before meeting for interactive further discussions, presumably led to a better preparation of the course and therefore a better and more meaningful in-class lecture with more focussed discussions and a higher value to the students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The BL format was evaluated very positively by the students through all three semesters; this again agrees with previous studies. [7][8][9][10] We think that a great impact to the successful implementation and acceptance of this delivery format was given by the predetermined order of action within the BL. The task to address the problem individually first, before meeting for interactive further discussions, presumably led to a better preparation of the course and therefore a better and more meaningful in-class lecture with more focussed discussions and a higher value to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Rovai and Jordan stated that BL is a flexible course design where online elements can be offered without completely losing face‐to‐face contacts; thus making it a robust educational tool. 5 In veterinary education, BL has been successfully integrated and well accepted by students, 6 , 7 , 8 , 9 , 10 and a survey in 2010 already pointed out a good acceptance of case‐based e‐learning. 11 However, there is only one study analysing the acceptance of an interdisciplinary case‐based BL course in veterinary education.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 Here we have shown that a dissection-based approach to teaching anatomy under expert supervision not only enhances relevant anatomical knowledge but is also valuable in improving dissection and technical communication skills, skills which are benificial throughout situations they may encounter in future and this triggers a needs based process for learning, thereby achieving better student engagement and learning. 1,2,4,5,10,11,24,25 Although anatomy is a knowledge-based subject, integrating clinical theme based cadaveric dissections can facilitate complementary development of dissection skills and technical communication in early stage veterinary students. Such an approach is also valuable in effectively achieving vertical integration across the veterinary curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Knowledge of anatomy is essential for understanding the relevance and application of the other pre/para clinical and clinical subjects taught in the veterinary curriculum. 1,2,[4][5][6][7][8] The knowledge of anatomy is classically gained by performing cadaveric dissections in the early years of the veterinary curriculum. 6,[9][10][11][12][13] However in recent years due to ethical, financial, time and infrastructure issues, the value of cadaveric dissections in anatomy teaching is increasingly questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Resources such as the use of live animals, cadavers, gross dissections, anatomic sections, and plastination enhance anatomic learning by researchers, students, and technicians [ 14 , 15 , 16 , 17 , 18 ]. In recent years, technological developments in the area of computer-assisted learning have improved anatomy teaching [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%